Telomere formation on macronuclear chromosomes of Oxytricha trifallax and O. fallax: alternatively processed regions have multiple telomere addition sites - Williams, Kevin R (BioMed Central, 2002)
BACKGROUND: Ciliates employ massive chromatid breakage and de novo telomere formation during generation of the somatic macronucleus. Positions flanking the 81-MAC locus are reproducibly cut. But those flanking the Common Region are proposed to often escape cutting, generating three nested macronuclear chromosomes, two retaining "arms" still appended to the Common Region. Arm-distal positions must differ (in cis) from the Common Region flanks. RESULTS: The Common-Region-flanking positions also differ from the arm-distal positions in that they are "multi-TAS" regions: anchored PCR shows heterogeneous patterns of telomere addition sites, but arm-distal sites do not. The multi-TAS patterns are reproducible, but are sensitive to the sequence of the allele being processed. Thus, random degradation following chromatid cutting does not create this heterogeneity; these telomere addition sites also must be dictated by cis-acting sequences. CONCLUSIONS: Most ciliates show such micro-heterogeneity in the precise positions of telomere addition sites. Telomerase is believed to be tightly associated with, and act in concert with, the chromatid-cutting nuclease: heterogeneity must be the result of intervening erosion activity. Our "weak-sites" hypothesis explains the correlation between alternative chromatid cutting at the Common Region boundaries and their multi-TAS character: when the chromatid-breakage machine encounters either a weak binding site or a weak cut site at these regions, then telomerase dissociates prematurely, leaving the new end subject to erosion by an exonuclease, which pauses at cis-acting sequences; telomerase eventually heals these resected termini. Finally, we observe TAS positioning influenced by trans-allelic interactions, reminiscent of transvection.